Transformational Leadership in Islamic Schools: Driving the Implementation of Child-Friendly School Initiatives: - - Wildan Azizy, Muhammad; Marno; Alfiana Yuli Efiyanti (Journal of Educational Management Research, 2025)
This study aims to analyze the role of madrasah principals' leadership in implementing the Child-Friendly School Program (Madrasah Ramah Anak), while also examining its impacts, supporting factors, and challenges. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis. Data analysis involved data reduction, data display, and conclusion drawing. The findings reveal that madrasah principals play multiple leadership roles—as educators, managers, supervisors, innovators, and leaders—in driving the implementation of child-friendly initiatives. The program is carried out systematically through daily habit-building activities, the provision of child-friendly infrastructure, and cross-sectoral collaboration. Positive impacts include increased student comfort, reduced bullying, heightened awareness of nutrition and hygiene, and the creation of a safe and inclusive school culture. Key enabling factors include regulatory support from the Ministry of Religious Affairs, active teacher participation, and partnerships with local health centers and law enforcement. However, the program faces several challenges, such as limited funding, teacher resistance to change, and difficulties in maintaining consistent implementation. These findings highlight the critical role of visionary leadership in transforming Islamic schools into safe, inclusive, and student-centered learning environments.